Effects of Substrate Composition and Subsurface Fluid Pathways on the Geochemistry of Seafloor Hydrothermal Deposits at the Lucky Strike Vent Field, Mid‐Atlantic Ridge. (5th May 2022) - Sánchez‐Mora, Dennis; Jamieson, John; Cannat, Mathilde; Escartín, Javier; Barreyre, Thibaut
Abstract: The Lucky Strike vent field, located on the Mid‐Atlantic Ridge (MAR), is hosted on enriched mid‐ocean ridge basalt associated with the nearby Azores hotspot. In this study, we present bulk rock geochemistry coupled with in situ sulfur isotope analysis of hydrothermal samples from Lucky Strike. We assess the geological controls on the differences in the major and trace element content and sulfur isotopic composition of the hydrothermal deposits within the vent field. The hydrothermal deposits contain elevated concentrations of elements typically enriched in mid‐ocean basalt (E‐MORB), such as Mo, Ba, and Sr, compared to typical values for other hydrothermal deposits hosted on the MAR. The range in sulfur isotope compositions of hydrothermal marcasite and chalcopyrite (−2.5 to 8.7‰) is similar to the range recorded at other sediment‐free basalt‐hosted seafloor hydrothermal sites. However, at Lucky Strike, the Capelinhos vent, situated 1.4 km east of the main field, is enriched in 34 S (by ∼3.5‰ for both marcasite and chalcopyrite), relative to the main field. This difference reflects contrasting subseafloor fluid/rock interactions at these two sites, including subseafloor sulfide precipitation at the main field that results in <20% of reduced sulfur within the upwelling hydrothermal fluid reaching the seafloor. We also compare the geochemistry of the hydrothermal deposits at Lucky Strike to other hydrothermal sites along the MAR and show that the average hydrothermal deposit Ba/Co is useful to discriminate between E‐MORB and other mafic/ultramafic hosted deposits. Plain Language Summary: We investigate the variations in composition of metal‐ and sulfur‐rich hydrothermal deposits that form on the seafloor at a cluster of high‐temperature hot springs called the Lucky Strike hydrothermal vent field, on the Mid‐Atlantic Ridge. We find that the mineralogy and geochemistry of the deposits do not vary spatially within this vent field. However, variations in the relative abundances of different sulfur isotopes within these deposits differ between the central cluster of vents and a newly discovered site called Capelinhos that is located 1.4 km east of the main vent field. Isotopic variations are usually interpreted to indicate differences in sulfur sources, with seawater and sulfur from the mantle as the two primary sources. However, our results instead show that significant mineral precipitation below the seafloor at the main vent cluster is the likely source of these isotopic variations. In addition, we show that the relative abundances of various trace elements within the hydrothermal deposits can be used to fingerprint the composition of the volcanic rocks that host these deposits. In particular, the ratio of Ba to Co can be used to fingerprint specific tectonic settings for different hydrothermal vent sites on mid‐ocean ridges. Key Points: Spatial variations in in situ sulfur isotope compositions at Lucky Strike indicate differences in fluid/rock interactions in the sub‐surface In situ sulfur isotope data suggests that >80% of the available H2 S in the ascending hydrothermal fluid has precipitated in the subseafloor The Ba/Co ratio of hydrothermal deposits discriminates those associated with enriched mid‐ocean basalts from other mafic/ultramafic hosted deposits